Metabolic Cost of Dendritic Ca2+ Action Potentials in Layer 5 Pyramidal Neurons - Yi, Guosheng; Fan, Yaqin; Wang, Jiang (Frontiers in Neuroscience, 2019)
Pyramidal neurons consume most signaling-related energy to generate action potentials (APs) and perform synaptic integration. Dendritic Ca2+ spike is an important integration mechanism for coupling inputs from different cortical layers. Our objective was to quantify the metabolic energy associated with the generation of Ca2+ APs in the dendrites. We used morphology-based computational models to simulate the dendritic Ca2+ spikes in layer 5 pyramidal neurons. We calculated the energy cost by converting Ca2+ influx into the number of ATP required to restore and maintain the homeostasis of intracellular Ca2+ concentrations. We quantified the effects of synaptic inputs, dendritic voltage, back-propagating Na+ spikes, and Ca2+ inactivation on Ca2+ spike cost. We showed that much more ATP molecules were required for reversing Ca2+ influx in the dendrites than for Na+ ion pumping in the soma during a Ca2+ AP. Increasing synaptic input increased the rate of dendritic depolarization and underlying Ca2+ influx, resulting in higher ATP consumption. Depolarizing dendritic voltage resulted in the inactivation of Ca2+ channels and reduced the ATP cost, while dendritic hyperpolarization increased the spike cost by de-inactivating Ca2+ channels. A back-propagating Na+ AP initiated in the soma increased Ca2+ spike cost in the apical dendrite when it coincided with a synaptic input within a time window of several milliseconds. Increasing Ca2+ inactivation rate reduced Ca2+ spike cost, while slowing Ca2+ inactivation increased the spike cost. The results revealed that the energy demand of a Ca2+ AP was dynamically dependent on the state of dendritic activity. These findings were important for predicting the energy budget for signaling in pyramidal cells, interpreting functional imaging data, and designing energy-efficient neuromorphic devices.